The welfare costs of HIV/AIDS in Eastern Europe: An empirical assessment using the economic value-of-life approach - Julia Fimpel; Michael Stolpe (Kiel Institute for the World Economy (IfW), 2006)
Based on the aggregation of individual willingness-to-pay for a statistical life, we calibrate an intertemporal optimization model to determine the aggregate welfare losses from HIV/AIDS in 25 Eastern European countries. Assuming a discount rate of three percent, we find a total welfare loss for the whole region of 1.2 trillion US-, approximately 16 percent of the region's annual GDP between 1995 and 2001. Although prevalence and incidence rates diverge sharply between countries with central Europe far less affected than the major countries in the Commonwealth of Independent States and the Baltics the epidemic is likely to spread to all countries unless a coherent strategy of prevention and treatment is backed up by substantial increases in health care investments. The sheer size of this task and the international nature of the epidemic render this one of the most important current challenges for all of Europe.
Keywords: I18; D91; J17; I12; 330; Survival Probabilities; Value of a Statistical Life; Willingness-to-Pay; Eastern Europe; HIV/AIDS; AIDS; Mensch; Bewertung; Wohlfahrtseffekt; Schätzung; Osteuropa